1998
DOI: 10.1046/j.1537-2995.1998.38998409004.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors influencing posttransfusion platelet increment in patients undergoing hematopoietic progenitor cell transplantation—a prospective analysis

Abstract: Platelet transfusion efficacy in hematopoietic progenitor cell transplant recipients is markedly influenced by clinical factors specific to the procedure as well as those already recognized in other settings. Alloimmunization is not, however, a major factor associated with a poor response to platelet transfusions after this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 26 publications
5
79
1
Order By: Relevance
“…This result is disappointing but not surprising, since Bishop et al 8 demonstrated that HSCT per se was independently associated with refractoriness to platelet transfusion, and Klumpp et al 6 reported a poor response to platelet transfusion in 64% of transplanted patients. Similar results were recently obtained by Ishida et al, 4 who observed a 16- The multivariate model included all 15 variables with a P value Ͻ0.2 at the univariate analysis. For all separators, the reported P value is for a test of whether each group is different from the Autopheresis-C group.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This result is disappointing but not surprising, since Bishop et al 8 demonstrated that HSCT per se was independently associated with refractoriness to platelet transfusion, and Klumpp et al 6 reported a poor response to platelet transfusion in 64% of transplanted patients. Similar results were recently obtained by Ishida et al, 4 who observed a 16- The multivariate model included all 15 variables with a P value Ͻ0.2 at the univariate analysis. For all separators, the reported P value is for a test of whether each group is different from the Autopheresis-C group.…”
Section: Discussionsupporting
confidence: 87%
“…The overall rate of alloimmunization in our patients was lower than that previously reported by Ishida et al 4 in adult subjects undergoing allogeneic or autologous HSCT (26.2%). This difference is even more evident considering de novo alloimmunization after HSCT (19.0% in the case series of Ishida).…”
Section: Leukemiacontrasting
confidence: 76%
See 3 more Smart Citations